(untitled) (Faridpur Medical College Journal, 2015)
Postoperative nausea and vomiting (PONV) is common after anaesthesia and surgery. In patients undergoing laparoscopic cholecystectomy (LC) without antiemetic prophylaxis, the incidence can be as high as 76% which would cause unexpected delay in hospital discharge. This study was designed to compare the efficacy of the ondansetron alone with combination of ondansetron and dexamethasone the given as prophylaxis for PONV in patients undergoing laparoscopic cholecystectomy. One hundred patients undergoing elective laparoscopic cholecystectomy were selected and randomly divided into 2 groups of 50 each. Group I received 4mg of ondansetron intravenously (iv), whereas Group II received ondansetron 4mg and dexamethasone 4mg just before induction of anaesthesia. Postoperatively, the patients were assessed for episodes of nausea, vomiting and need for rescue antiemetic. Complete response defined as no nausea and vomiting during first 24 hours, was noted in 76% of patients in Group I and in 92% of patients in Group II. Rescue anti emetic requirement was less in Group II (4%) than Group I (20%). So it can be concluded that the combination of ondansetron and dexamethasone is more effective in preventing PONV in patients undergoing laparoscopic cholecystectomy than ondansetron alone. Faridpur Med. Coll. J. 2014;9(1): 3-6